DINAMIKA KELOMPOK DAN TINGKAT ADOPSI PENGELOLAAN TANAMAN TERPADU (PTT) PADI PADA KELOMPOK TANI DI DESA ARJASA KECAMATAN ARJASA KABUPATEN JEMBER - Anik Susilowati; Lenny Widjayanti; Djoko Soejono (University of Jember, 2017)
Food crops, especially rice, are the main crops cultivated by most Indonesian farmers. One of the strategies taken by the government to increase rice production in Indonesia is through Integrated Crop Management Field School (ICMFS) program. The success of the development program can be seen from the approach within the group. Farmer groups have a strategic position in realizing the application of integrated cultivation, therefore every farmer has different adoption level in applying ICM. The purpose of this study is to: (1) the dynamics of groups in farmer groups in Arjasa, (2) the adoption of Integrated Crop Management of rice at farmer group at in Arjasa, (3) the relationship between socio-economic factors with the adoption ICM of rice in Arjasa. Determination of research area using Purposive Method. The method used in this research is descriptive and correlation. Sampling method using Purposive Sampling and Proporsinate Random Sampling. Methods of data collection using structured interviews, observation, document. Analyzer used is Likert scale and Rank Spearman correlation. The results showed: (1) the dynamics of farmer groups in Arjasa as a whole is dynamic. (2) the adoption of Integrated Crop Management (ICM) of rice in the farmer group in Arjasa as a whole is high (3) there is a significant correlation between age factor and experience with ICM adoption. While the factors of education, land area, income, and information sources do not have a significant relationship with the adoption of ICM